Planning for the Accelerated Education Programme for Refugee Learners in Uganda: Stakeholders Experiences - Kiiria, Grace; Eduan, Wilson; Eduan, Stella (East African Journal of Education Studies, 2024)
This study focused on Accelerated Education Programme (AEP) to develop planning and coordination models tailored to this kind of programme. The specific objective of the study was: To explore stakeholder’s experiences in planning for AEP to enhance transition of refugee learners to secondary education. The study sought to explore how stakeholders experience planning and how planning influences transition of refugees learners to secondary education based on grounded theory design. Data collection was done through in-depth interviews and constant comparison analysis were done. The findings indicate that planning for AEPs was based on the four major aspects: planning for programme support, the beneficiaries, stakeholder engagement and harmonizing the curriculum. However, there is a gap in how planning is done which negatively influences transition of AEP learners to secondary education. The above factors need to be taken into consideration right from the initial stages of the programme. A Community-Focused Planning Model was developed from the study- a model which upholds the significance of community focused planning with emphasis on taking into consideration the socio-ecological environment/community in which the child lives while planning for AEP. The study therefore contributes to improved planning of AEPs while taking into consideration the needs of refugee learners, the environment in which they live and collaboratively engaging communities in the design of AEP. Thus, leading to improved learning outcomes and transition of refugee children to secondary education